Radiology teacher: a free, internet-based radiology teaching file server. - Talanow R (Journal of the American College of Radiology, 2009)
Teaching files are an essential ingredient in residency education. The online program Radiology Teacher was developed to allow the creation of interactive and customized teaching files in real time. Online access makes it available anytime and anywhere, and it is free of charge, user tailored, and easy to use. No programming skills, additional plug-ins, or installations are needed, allowing its use even on protected intranets. Special effects for enhancing the learning experience as well as the linking and the source code are created automatically by the program. It may be used in different modes by individuals and institutions to share cases from multiple authors in a single database. Radiology Teacher is an easy-to-use automatic teaching file program that may enhance users' learning experiences by offering different modes of user-defined presentations.